PENERAPAN PEMBELAJARAN KOOPERATIF DENGAN TEKNIK MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA - Dewi Hernia Nengsih (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
Mathematics in the unit of measurement material. One effort to overcome this error is by applying cooperative learning to make a match techniques. The selection of cooperative learning models is based on the learning interactions that arise. Through cooperative learning, a student will become a learning resource for other friends. So the purpose of this study was to improve the activity and learning outcomes of mathematics through cooperative learning with make a match technique in class VI SD Negeri 49 Kendari. This study uses a class action research design, carried out in a spiral form, consisting of four main activities namely planning, implementation, observation, and reflection carried out in 3 cycles. Data analysis techniques in this study are descriptive qualitative analysis and quantitative analysis. This study used to test and non-test instruments, which were collected using learning outcomes test questions, observation sheets, and documentation of learning activities. The results of data analysis show that cooperative learning with make a match technique can increase the activity and learning outcomes of class VI students at SD Negeri 49 Kendari.